Pretest-post-test evaluation with lay midwives in remote Guatemala after educational activities about COVID-19 - Kimberly Garcia; Argelia Rodriguez; Zoila Gonzalez; Cheryl Armstrong; Eli Iacob; Emily Flynn; Molly Simmons (James Cook University, 2024)
Introduction: Guatemalan lay midwives are well-respected community leaders in a country that lacks the institutional capacity to meet healthcare needs related to pregnancy, newborns, and COVID-19. Thus, Guatemalan lay midwives, who attend the majority of births in their country and who attend most births at home, are in an optimal position to offer frontline support to pregnant women and newborns regarding the global pandemic. The primary objective of this program of study was to dispel myths about COVID-19 and to provide culturally relevant educational activities to low-literacy Guatemalan lay midwives about issues related to the virus, such as signs and symptoms, risks to the mother and fetus, which patients are most vulnerable, appropriate responses, benefits and side-effects of the vaccine, timing of the vaccine, how the virus interacts with breastfeeding, and breastfeeding recommendations. Methods: In a partnership among the Guatemalan Ministry of Health, expert faculty at the University of Utah College of Nursing, and Madre y Niño, a non-profit organization from the US, evidence-based educational activities about COVID-19 were offered orally in the native language of participants. Two hundred and ten lay midwives attended educational sessions at 11 locations throughout the remote Peten department. Educational activities included repetition, storytelling, and role plays. A pretest-post-test evaluation of 10 questions with 24 correct answers was used to determine if the educational activities changed lay midwife knowledge about COVID-19. Participants were given essential birth supplies and laminated COVID Reminder Cards, which were designed to increase visual literacy, to encourage knowledge retention after the educational sessions. Results: Participants showed a significant increase in knowledge scores (possible 0-24) from prescores 7.09 (standard deviation (SD)=3.06) to 15.20 (SD=4.61), Student's t-test p<0.001. In addition, a significantly higher proportion of participants mistakenly thought COVID-19 passed through breast milk on the pretest (70.1%) compared to post-test (8.4%) (McNemar test, p<0.001). Regarding breastfeeding, 12.6% of participants knew on the pretest that women with COVID-19 who breastfeed should wear a mask and wash their hands compared to 74.3% of participants who knew these recommendations on the post-test (Wilcoxon signed-rank test, p<0.001). Finally, 2% of participants knew on the pretest that pregnant women with COVID-19 should take a low-dose aspirin compared to 67% of participants on the post-test (χ² (1)=194.7, p<0.001). Conclusion: These essential primary care providers misunderstood many critical issues related to COVID-19, pregnancy, and newborns. Culturally relevant educational activities provided orally in the native language of participants dispelled myths about the virus and significantly improved lay midwife knowledge. Providing evidence-based educational activities in a culturally relevant format is critical to protecting remote, vulnerable populations, such as pregnant Guatemalan women and newborns, during a global pandemic.